Addendum to Killeen's (2019) Bidding for Delayed Rewards. Issue 3 (30th April 2020) - Killeen, Peter R.
Abstract : Killeen (2019) portrayed an intimate relation between diverse economic indices, in particular compensation functions, discount functions, and demand functions. The article bemused some experts, however, by its counterintuitive prediction of an increase in the amount bid as the delay increased. Furthermore, the article failed to provide an explicit treatment of the small–soon versus large–late choice paradigm, to cite several papers that provided precedent for the current work, and to demonstrate the adequacy of his expenditure functions for data on purchasing decisions. These shortcomings are remedied in the current note, and some additional extensions offered.